Peningkatan Kapasitas Masyarakat melalui Pelatihan Pembuatan Bioenzim dan Mikroorganisme Lokal di Desa Karangjaya, Cianjur - Purwakusuma, Wahyu; Purwawangsa, Handian; Eka Maulidiya, Sherly; Amirah, Nurul; Setiawan, Dani; Junjunan, Katresna; Pratama, Muhamad Rizki Hadi; Azis, Nadya Nurpalah; Maulana, Fauziah Azzahra; Hermawan, Akbar (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
Karangjaya Village, located in Pasirkuda District, Cianjur Regency, has significant potential in the field of sustainable agriculture, particularly in avocado and coffee commodities. The village has a cool climate, high rainfall, and fertile soil, making it ideal for developing high-quality agricultural products. The community service program implemented in Karangjaya Village focuses on environmentally friendly innovations by producing bioenzymes and local microorganisms (MOL). This training aims to provide knowledge and practical skills to the Forest Farmers Group in the village, consisting of 40 participants, to support farming efficiency while maintaining soil ecosystem balance. The implementation of the training follows four main stages: socialization, training, practice, and evaluation. Participants are taught how to utilize organic materials, such as fruit and vegetable waste, and other local materials to produce bioenzymes and MOL through a simple fermentation process. Evaluation results show a significant increase in participants' understanding. Pre-test and post-test results indicate an average improvement of 62-85%, particularly in the material related to the production and benefits of bioenzymes as organic fertilizers. This program has proven effective in enhancing farmers' capacity to adopt environmentally friendly technology. However, further assistance is needed to deepen technical understanding related to the use of bioenzymes and the application of MOL. This program shows that bioenzyme and MOL innovations have great potential to support sustainable agriculture in Karangjaya Village, increase crop yields, reduce organic waste, and strengthen the community's welfare. With these strategic steps, Karangjaya Village can become a model of an innovative, competitive agricultural village.